2015
DOI: 10.1080/15287394.2015.1104525
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hexavalent chromium-induced genotoxic damage in peripheral blood of mice by epigallocatechin-3-gallate (EGCG) and its relationship to the apoptotic activity

Abstract: This study was conducted to investigate the relationship between modulation of genotoxic damage and apoptotic activity in Hsd:ICR male mice treated with (-)-epigallocatechin-3-gallate (EGCG) and hexavalent chromium [Cr(VI)]. Four groups of 5 mice each were treated with (i) control vehicle only, (ii) EGCG (10 mg/kg) by gavage, (iii) Cr(VI) (20 mg/kg of CrO3) intraperitoneally (ip), and (iv) EGCG in addition to CrO3 (EGCG-CrO3). Genotoxic damage was evaluated by examining presence of micronucleated polychromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…This proposal is consistent with our results since the frequencies of apoptotic cells (particularly, late apoptotic cells) indeed increased signiicantly with the administration of vitamin C, and their administration prior to treatment of V 2 O 5 increased them even further [8]. Additionally, other studies have reported that the apoptosis-inducing activity of antioxidants might be synergistically enhanced by a combined treatment with chemopreventive [44] or genotoxic agents [40]. Therefore, it is plausible that enhanced induction of apoptosis following a combined treatment may positively contribute to the elimination of the cells with V 2 O 5 -induced DNA damage (MN-PCE).…”
Section: Protective Efects Of Vitamin C Against Genotoxic Damage Fromsupporting
confidence: 81%
See 1 more Smart Citation
“…This proposal is consistent with our results since the frequencies of apoptotic cells (particularly, late apoptotic cells) indeed increased signiicantly with the administration of vitamin C, and their administration prior to treatment of V 2 O 5 increased them even further [8]. Additionally, other studies have reported that the apoptosis-inducing activity of antioxidants might be synergistically enhanced by a combined treatment with chemopreventive [44] or genotoxic agents [40]. Therefore, it is plausible that enhanced induction of apoptosis following a combined treatment may positively contribute to the elimination of the cells with V 2 O 5 -induced DNA damage (MN-PCE).…”
Section: Protective Efects Of Vitamin C Against Genotoxic Damage Fromsupporting
confidence: 81%
“…This was probably because the vitamin C acted as a potent antioxidant (reducing agent) that scavenged free radicals of reactive oxygen and nitrogen species and prevented them from damaging nucleic acids [27,37]. Interestingly, the MN-PCE decrease we observed with vitamin C was more efective than with the administration of beverages with high levels of antioxidants such as green tea [38], red wine [39] and their antioxidant components such as polyphenols [40][41][42].…”
Section: Protective Efects Of Vitamin C Against Genotoxic Damage Frommentioning
confidence: 93%
“…Some catechins, including EGCG, possess an esterified gallate moiety at the third position of the C ring, the catechol group on the B ring and the OH groups at the fifth and seventh positions on the A ring (Figure 2 II). The potential free radical scavenging activity of EGCG has been attributed to the presence of the gallate group [10,27].…”
Section: Oxidative Stress Antioxidants and Green Tea Flavonoidsmentioning
confidence: 99%
“…The high mobility, solubility and bioavailability of Cr(VI) compounds increase risk in human populations [36,[43][44][45][46]. There are three ways in which Cr(VI) could induce effects on human health: first, by the generation of •OH (oxidative stress); second, by the modification of antioxidant enzymes like SOD, CAT and peroxidase (POX) [10,36,46]; and finally, by the intervention of non-oxidative mechanisms of Cr(VI) [47].…”
Section: Genotoxic Roles Of Chromium and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation